PENERAPAN BIMBINGAN KONSELING QUR’ANI UNTUK MENINGKATKAN JIWA RELIGIUS SISWA DI MADRASAH TSANAWIYAH NEGERI 2 KOTA TANGERANG - Mohamad Zaenal Arifin; Elmi Khoirunisa (Institut Binamadani Indonesia, 2026)
This study aims to describe the implementation of Qur'anic guidance and counseling in improving the religious spirit of students at MTs Negeri 2 Tangerang City, as well as to identify supporting and inhibiting factors. The background of the study is based on the phenomenon of low religious discipline and religious behavior among some students, which is influenced by the environment, social interactions, and a lack of spiritual guidance. The research method used was qualitative, with data collection techniques through observation, interviews, and documentation. Data sources included Guidance and Counseling (BK) teachers, Islamic Religious Education teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that Qur'anic guidance and counseling at MTs Negeri 2 Tangerang City is implemented through various activities, such as Quranic literacy, stimulating discussion groups, involving students in worship activities, and involving parents. This study concludes that Qur'anic guidance and counseling can improve students' awareness of worship, discipline, empathy, and Islamic behavior at school. This is inseparable from supporting factors such as the teachers' strong commitment to instilling Quranic values, students' enthusiasm for spiritual activities, and a madrasa curriculum that is open to an integrative approach.